Conditional betas and Market re-definition: Revisiting the capital asset pricing model with Mexican data - Treviño Villarreal, María de Lourdes (International Research Journals, 2012)
This paper examined the time-series cross-section relation between conditional betas and stock returns using monthly data for Mexico for the period January 1999 to August 2008. The portfolio-level analysis and regressions indicated a positive relation between conditional betas and the expected returns. The two proxies for a more complete market return measure, the labor income beta and the foreign stockmarket return, proved significant, adding explanatory power to the models. The results suggested, however, that it is necessary to allow for time variations in betas as well in order to explain the variations of the monthly average returns. A size effect was also found, although it is not very important. In spite of the empirical support found for the conditional CAPM over the static CAPM, both specifications explain about half of the monthly average return variation, which calls for differences in the pricing of risk between developed and emerging countries